2018
DOI: 10.15294/jpii.v7i4.10684
|View full text |Cite
|
Sign up to set email alerts
|

The Determinant Factors Analysis of Indonesian Students’ Environmental Awareness in PISA 2015

Abstract: This research intended to reveal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…learning models can also be influenced by student characteristics, one of which is self-efficacy (Aharony & Gazit, 2020;Hasyim & Eldiana, 2020;Wong et al, 2020). The term "self-efficacy" is used to describe students' beliefs that their actions can produce something desired such as solving problem difficulties, confidence in the chosen answer or achieving goals (Susongko & Afrizal, 2018;Latifah et al, 2019;Mayasari et al, 2019). Self-efficacy plays an important role in stimulating students to increase their sense of enthusiasm in learning (Sökmen, 2021;Zysberg & Schwabsky, 2020;Gundel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…learning models can also be influenced by student characteristics, one of which is self-efficacy (Aharony & Gazit, 2020;Hasyim & Eldiana, 2020;Wong et al, 2020). The term "self-efficacy" is used to describe students' beliefs that their actions can produce something desired such as solving problem difficulties, confidence in the chosen answer or achieving goals (Susongko & Afrizal, 2018;Latifah et al, 2019;Mayasari et al, 2019). Self-efficacy plays an important role in stimulating students to increase their sense of enthusiasm in learning (Sökmen, 2021;Zysberg & Schwabsky, 2020;Gundel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In Oztürk (2018) study based on the PISA 2015 data, it was determined that for different socioeconomic levels there were significant relationships between scientific literacy and environmental awareness, and between scientific literacy and environmental optimism. In a study by Susongko and Afrizal (2018) using the PISA 2015 data for Indonesian students, it was concluded that environmental awareness was related to the students' enjoyment of learning science, their self-efficacy in science, their instrumental motivation, inquiry-based instruction in science learning, and their science proficiency and epistemic beliefs. In Lau and Lam (2017) study, according to the PISA 2015 data, adaptive instruction, teacher-directed instruction and interactive application were positively correlated with science performance in all regions.…”
Section: Discussionmentioning
confidence: 99%
“…The education system must be developed according to the needs and developments. One of the factors that support development is education (Sujatmiko et al, 2019;Susongko & Afrizal, 2018;Syarifudin, 2020). Education is inseparable from learning activities in schools.…”
Section: Introductionmentioning
confidence: 99%